A modified Sequential Organ Failure Assessment score using the Richmond Agitation-Sedation Scale in critically ill patients - Viglino, Damien; Maignan, Maxime; Debaty, Guillaume (Journal of Thoracic Disease; Vol 8, No 3 (March 18, 2016): Journal of Thoracic Disease, 2016)
In the January 2016 issue of Critical Care Medicine, Vasilevskis et al. (1) reported the validation study of a modified Sequential Organ Failure Assessment (SOFA) score using the Richmond Agitation-Sedation Scale (RASS) (2) instead of the Glasgow Coma Scale (GCS) for the neurological component. As explained by the authors, the SOFA score, first shown to describe multiple organ failure in patients with sepsis, is now widely used for risk stratification in a wide panel of ICU patients. Unfortunately, the GCS component is subject to implementation difficulties for some patients, such as those who are intubated, and is not highly reliable when assessing neurologic disorders such as delirium and agitation.